Симультанні операції у пацієнтів із жовчнокам’яною хворобою та хірургічною патологією ендокринних органів - Павловський, М. П.; Коломійцев, В. І.; Сироїд, О. М.; Гавриш, Я. І. (Clinical Endocrinology and Endocrine Surgery, 2010)
The peculiarities of performance and results of simultaneous operations (SO) in patients with cholelithiasis (ChL) and surgical diseases of endocrine organs were analyzed in this study. 142 patients with combined biliary and endocrine pathology at the age of 26–74 y.o. were operated during 2000–2009 period. SO performed in 52 (36.6%) patients (SO-group). The stepwise of surgical treatment used in 90 (63.4%) patients (control group). SO were performed in patients with II–III classes of ASA classification and compensation of metabolic dysfunctions without severe complications of ChL, and with benign endocrine diseases. The laparoscopic cholecystectomy (LCE) and laparoscopic/endoscopic adrenalectomy were performed in 13 (25.0%) patients of SO-group, LCE and thyroid surgery (thyroidectomy, hemithyroidectomy) — in 36 (69.2%), LCE and parathyroidectomy — in 3 (5.8%) cases. LCE were performed at 45 (50.0%) patients of control group, thyroidectomy — at 36 (40.0%), parathyroidectomy — at 5 (5.6%), adrenalectomy — at 4 (4.4%) patients. Five (9.6%) patients of SO-group and seven (7.8%) patients of control group had postoperative complications (p=0,696). There was no mortality. The use of SO for treatment of patients with ChL and combined surgical pathology of endocrine organs favoured to the good immediate results.